(untitled) (Research, Society and Development, 2022)
This work aims to evaluate the indicators of urban services and quality of life for the Brazilian city of Cuiabá-MT, through the application of Brazilian code NBR ISO 37120, with a subsequent comparative approach to the city of Rio de Janeiro-RJ, the only Brazilian city that already has a similar study. The comparison establishment between communities is justified to provide subsidies and to share good practices, contributing to the construction of knowledge, which is still incipient in the Brazilian scope, since no Brazilian municipality has yet officially released its indicators based on this code. The NBR ISO 37120 is based on 100 indicators in 17 thematic axes, with 40 indicators in 11 thematic axes being addressed in this research, as followed indicated: Economy, Energy, Governance, Health, Safety, Solid Waste, Telecommunications and Innovation, Transport, Urban Planning, Water and sanitation, and Sewers. The results show that the main differences between the two cities are in Transport, Urban Planning, Sewers and Water and Sanitation. Under the importance of the theme, it is suggested to the city council the use of indicators as an instrument of permanent management, since its quantification helps in municipal decisions, allowing to assess the deficiencies and qualities of the municipality’s management.